AI-BASED PERSONALIZED LEARNING MODELS IN A DIGITAL EDUCATIONAL ENVIRONMENT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article analyzes the issues of creating personalized learning models based on the integration of artificial intelligence (AI) technologies within a digital educational environment. It explores the possibilities of organizing an educational process adapted to students' knowledge levels, interests, and learning paces using modern AI solutions. Furthermore, the effectiveness of AI-based adaptive learning systems and their contribution to the development of digital education are evaluated and analyzed.
Keywords: digital education, artificial intelligence, personalized learning, adaptive teaching, pedagogical technologies, digital platforms.